Inclusivity in Focus: Patterns, Progress, and Pathways in Diversity Marketing Research – A Bibliometric Analysis - Chotisarn, Noptanit; Thonglor, Ratchamongkhon; Phuthong, Thadathibesra (International Review of Management and Marketing, 2025)
Drawing from 270 studies in the Scopus database, this study conducts a comprehensive bibliometric analysis of diversity marketing research from 2004 to 2024. Specifically, we analyze the publication patterns, co-authorship networks, research clusters, citation patterns, and keyword co-occurrences in order to map the evolution of this field. Based on the findings, there are three distinct development phases: Foundational conceptualization (2004- 2010), theoretical development (2011-2017), and methodological sophistication (2018-2024). Additionally, the geographic analysis showed that such research is mainly concentrated in Western institutions, with contributions from emerging Asian markets, while the citation analysis identified four interconnected research clusters: Cross-cultural foundations, inclusive strategies, ethnic consumer behavior, and emerging market dynamics. Overall, the results suggest that methodological sophistication and theoretical integration should be increased, especially in digital transformation and cultural representation. This evolution also highlights the need for more diverse collaborative research and standardized effectiveness metrics, especially in today’s increasingly connected global marketplace.